The concept of justice in the philosophy of Ronald Dworkin (قضايا سياسية, 2024)
Ronald Dworkin develops his theory of justice within a frame of reference of liberal theoretical attempts - which John Rawls had begun in the 1970s - to reform political philosophy and the theory of justice in particular in order to enhance the legitimacy of the liberal political and economic system, to be reconsidered and formulated on the basis of justice (justice Redistribution of resources).Through his theory of justice, Ronald Dworkin tried to reconcile, on both the theoretical and practical levels, the concepts of liberty and equality. At the theoretical level, no political theory can be worthy of attention unless it acknowledges the complementarity of these two values. One of them is indispensable for the other, but on the practical level, the political reality is not characterized by political legitimacy unless it achieves liberty and equality, as it cannot achieve the requirements of its citizens if one of these two values is given priority over the other. Therefore, the long struggle between advocates of equality on the one hand, and Liberty advocates, on the other hand, regarding the priority of any of the two values over the other is baseless, and based on the above, this study deals with Ronald Dworkin’s theory of justice based on the unity of the concepts of liberty and equality, in what he called “the unity of values thesis,” and how to employ it in the political and economic field.